Physiological and Physicochemical Changes during Ripening of Tomato Fruit (Assila) Under Greenhouse and Ambient Temperature - Adamu, Labaran Alhassan (2018)
A thesis submitted to the Department of Food Science and Technology, College of Science, in partial fulfilment of the requirements for the degree of Master of Science in Food Science and Technology.